2021
DOI: 10.5398/tasj.2021.44.3.307
|View full text |Cite
|
Sign up to set email alerts
|

Feed Intake, Nutrient Digestibility, Antioxidant Activity in Plasma, and Growth Performance of Male Dairy Cattle Fed Black Rice and Purple Corn Extracted Residue

Abstract: The study aimed to evaluate the impact of black rice and purple corn extracted residue (BPER) on feed intake, nutrient digestibility, growth performance, and antioxidant activity in male dairy cattle. The residue after extraction of anthocyanin from black rice and purple corn contains anthocyanin and phenolic acids. Several researchers found that anthocyanins and phenolic acids had antioxidant and antimicrobial functions in animals. Sixteen male dairy cattle (with average body weight of 160 ± 10.6 kg) were all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
5
10
0
Order By: Relevance
“…In this work, we investigated a novel type of corn with cobs rich in anthocyanin as roughage in feedlot lamb diets in comparison to regular corn cobs and commonly used grass hay for comparison. In accordance with the literature ( Prommachart et al, 2021b ; Antunović et al, 2022 ; Tian et al, 2022 ), there was no effect of dietary anthocyanin on lamb DMI and growth performance. Prommachart et al (2021b) also found no differences in DMI when black rice and purple corn-extracted residue were tested in the diets of male dairy cattle.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this work, we investigated a novel type of corn with cobs rich in anthocyanin as roughage in feedlot lamb diets in comparison to regular corn cobs and commonly used grass hay for comparison. In accordance with the literature ( Prommachart et al, 2021b ; Antunović et al, 2022 ; Tian et al, 2022 ), there was no effect of dietary anthocyanin on lamb DMI and growth performance. Prommachart et al (2021b) also found no differences in DMI when black rice and purple corn-extracted residue were tested in the diets of male dairy cattle.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with the literature ( Prommachart et al, 2021b ; Antunović et al, 2022 ; Tian et al, 2022 ), there was no effect of dietary anthocyanin on lamb DMI and growth performance. Prommachart et al (2021b) also found no differences in DMI when black rice and purple corn-extracted residue were tested in the diets of male dairy cattle. Antunović et al (2022) observed no influence of red corn rich in anthocyanins in lamb diets on final BW, ADG, and DMI.…”
Section: Discussionsupporting
confidence: 91%
“…Antioxidant activity of milk after supplementation of feed with natural plant additives (own work based on:[140,[160][161][162][163][164][165][166][167][168][169][170]). …”
mentioning
confidence: 99%
“…Anthocyanins are also known to impact the composition and quantity of ruminal bacterial species through specific inhibition or selective augmentation of particular species growth. Thus, anthocyanins can influence rumen fermentation characteristics because they have substantial regulatory effects on ruminal bacteria, hence promoting gastrointestinal tract health [ 13 ]. Additionally, anthocyanins have strong antioxidant qualities that can protect the organism from peroxidation damage, hence improving the rumen microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…However, as Purple Neem foliage has a bitter taste, the use of sunflower oil (SFO) as an additive increases the feed intake and palatability of the ruminant. Here, SFO has beneficial properties as a source of fatty acids and as a good source of fatty acids and to convert monounsaturated fatty acids (MUFAs) to polyunsaturated fatty acids (PUFAs) or inserting new unsaturated links into previously existing unsaturated bonds to improve products, such as meat and milk [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%